QUASI-STATIC MODEL OF COLLIMATED JETS AND RADIO LOBES. I. ACCRETION DISK AND JETS - Colgate, Stirling A.; Fowler, T. Kenneth; Li, Hui; Pino, Jesse (The Astrophysical journal, 2014)
This is the first of a series of papers showing that when an efficient dynamo can be maintained by accretion disks around supermassive black holes in active galactic nuclei, it can lead to the formation of a powerful, magnetic helix that could explain both the observed radio jet/lobe structures on very large scales and ultimately the enormous power inferred from the observed ultra-high-energy cosmic rays. In this work, we solve a set of one-dimensional equations similar to the steady-state standard accretion disk model, but now including the large-scale magnetic fields giving rises to jets. We find that the frequently made assumption that large-scale fields are frozen into the disk is fundamentally incorrect, due to the necessity for current and the accreting mass to flow perpendicular to magnetic flux surfaces. A correct treatment greatly simplifies the calculations, yielding fields that leave the disk nearly vertically with magnetic profiles uniquely determined by disk angular momentum conservation. Representative solutions of the magnetic fields in different radial regions of the disk surface are given, and they determine the overall key features in the jet structure and its dissipation, which will be the subjects of later papers.